PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PELAPORAN MASYARAKAT UNTUK KERUSAKAN JALAN DI PALEMBANG MENGGUNAKAN GOOGLE MAPS API - Andri Purwansyah; Afriyudi Afriyudi; Suyanto Suyanto (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2020)
In reporting road damage to the Palembang Bina Marga, the road broom team did still have shortcomings because the reporting that was done was not efficient because the reports in the form of photographs had to be printed first and then given to the officers in the bina marga. The purpose of this study was to design and build a road damage reporting system at the Highways of Palembang city with reports that in the form of direct report photos can be sent to the website and officers can display reports that have been received directly to the DGH field. With the existence of web-based road damage reporting using Google maps the API that activates GPS can make it easier to find location points about road damage so that people can immediately report via smartphone which was developed using web-responsive methods aimed at providing an optimal surfing experience in various devices and expected can help the government and the people of Palembang city in an effort to pay attention to the road conditions around.